Simulation study of compound parabolic collector‐based solar water heating system with thermal energy storage. Issue 3 (23rd December 2021) - Christopher, S.; Kumaresan, V.
Abstract: Solar water heating (SWH) systems becomes increasingly popular in modern buildings, due to significant reduction in energy consumption in heating applications. In this work, an active SWH is modeled using TRNSYS software for climatic conditions of Chennai, India, employing an external compound parabolic concentrator solar collector and stratified thermal storage system (STESS). The performance parameters are estimated on the basis of monthly and annual averaged solar fractions (SF) by varying the collector area, mass flow rate, various controller strategies, and STESS geometry. The simulated studies have specified the ability of the optimized system to supply the hot water demand of 280 L d −1 at 60°C, attaining a SF of 0.97. This design strategy can be implemented for the development of an efficient SWH system, utilizing zero energy consumption from conventional resources. The proposed TRNSYS model has been validated using experimental data under similar test conditions. An influence of placing XCPC under evacuated tubes is simulated, resulting 5% improvement in energy gained over an evacuated tube solar collector without XCPC.